'Imaginary' illnesses? Worker occupational health and privatized health care: Sri Lanka's story. Issue 2 (3rd April 2019) - Ruwanpura, Kanchana N.
Abstract : Sri Lankan apparel factories claim to be at the vanguard of ethical production on the global supply chain. Both to produce this image and to project their status as fair employers, industrialists offer health services at factory settings. This article focuses on two factory sites that have permanent qualified nurses to attend to illness and injuries, and medical doctors that visit twice a week. While on the face of it, these efforts are commendable, what my fieldwork signalled was that occupational health issues were inseparable from the creeping privatization of health care systems. Injuries or illnesses not treated within a 'reasonable' time frame were invariably referred to the private clinics of medical doctors. Ironically, this pattern is bolstered by the proliferation of what one worker described as 'imaginary' illnesses – that is, illnesses that workers concoct as a form of respite from the intense pressures of working in this sector. In this paper, I examine the ways in which workers get treated and how it is connected to an increasingly unregulated privatized landscape of healthcare. These shifts also show how the perspectives of citizenry change, despite the social welfare achievements around health and longevity of Sri Lankans.